Efektivitas Perangkat Pembelajaran Berbasis Masalah Berbantuan Laboratorium Virtual Untuk Meningkatkan Kemampuan Pemecahan Masalah Peserta Didik - Indah Putri Aprilianti; Ahmad Harjono; Ni Nyoman Sri Putu Verawati; Jannatin 'Ardhuha (Universitas Hamzanwadi, 2024)
This research aims to produce an effective tool for improving students' physics problem solving abilities. The learning tool developed uses a problem-based learning model with the help of a virtual laboratory to improve students' problem solving abilities. The research design used is 4D model development research consisting of Define, Design, Develop, and Disseminate. The products developed are Syllabus, RPP, LKPD, Teaching Materials, Learning Media, and Problem Solving Ability Test Instruments. The data collection technique uses the N-Gain test and is interpreted into an interpretation of effectiveness. Improving students' problem solving abilities from the results of this research shows that the N-Gain test value is 0.72 in the high category. Based on this research, it can be concluded that problem-based learning tools assisted by virtual laboratories are effective in improving students' problem-solving abilities